Mapping the Rehabilitation Interventions of a Community Stroke Team to the Extended International Classification of Functioning, Disability and Health Core Set for Stroke - Evans, M; Hocking, C; Kersten, P (Taylor and Francis, 2016)
Purpose: This study aim was to evaluate if the Extended International Classification of Functioning, Disability and Health Core Set for Stroke captured the interventions of a community stroke rehabilitation team situated in a large city in New Zealand. It was proposed that the results would identify the contribution of each discipline, and the gaps and differences in service provision to Māori and non-Māori. Applying the Extended International Classification of Functioning, Disability and Health Core Set for Stroke in this way would also inform whether this core set should be adopted in New Zealand. Method: Interventions were retrospectively extracted from 18 medical records and linked to the International Classification of Functioning, Disability and Health and the Extended International Classification of Functioning, Disability and Health Core Set for Stroke. The frequencies of linked interventions and the health discipline providing the intervention were calculated. Results: Analysis revealed that 98.8% of interventions provided by the rehabilitation team could be linked to the Extended International Classification of Functioning, Disability and Health Core Set for Stroke, with more interventions for body function and structure than for activities and participation, no interventions for emotional concerns and limited interventions for community, social and civic life. Results support previous recommendations for additions to the EICSS. Conclusions: The results support the use of the Extended International Classification of Functioning, Disability and Health Core Set for Stroke in New Zealand, and demonstrates its use as a quality assurance tool that can evaluate the scope and practice of a rehabilitation service.
Keywords: Extended International Classification of Functioning Disability and Health Core Set for Stroke; Community stroke rehabilitation; New Zealand; Quality assurance